"Revaluing Prosper of Aquitaine in Contemporary Liturgical Theology". (September 2014) - Novak, Joseph A.
Contemporary liturgical theologians rely upon the now classic passage from Prosper of Aquitaine—ut legem credendi lex statuat supplicandi—as a foundation for much of their constructive proposals. However, the competing interpretative approaches to Prospers adage have threatened its integrity by either expecting too much or too little from the phrase. This essay argues for a renewed examination of Prospers writings and proposes a new method of interpretation, one that addresses both the immediate concerns of Prosper and the aims of contemporary liturgical theologians. This new interpretative scheme views liturgical practice, Holy Scripture, and Church tradition as the necessary components in deriving the Prosperian lex supplicandi. In revisiting Prospers writings to validate this thesis, this essay provides an exhaustive map of three major interpretation camps of Prospers phrase, and suggests a fourth approach.